RESULTS ON DEVELOPMENT OF MONITORING TOOLS FOR STORAGE GRAIN INSECTS (Mongolian Journal of Agricultural Sciences, 2015)
For the purpose of monitoring poisonous insects in storage of grain, flour mills, food industry, and plant originated products it was developed a rapid method to reveal it and insects’ density, distribution, level of harm and control method was determined. Two different pest traps were developed: paper trap and cylinder trap. Results of experimental study showed that these traps were suitable in order to reveal and catch the pests and possible for the use in monitoring studies for the storage poisonous insects. The distribution and density of poisonous insects was established using these traps. The number of caught poisonous insect and their distribution was established by the method of G.A. Zakladnoi and level of harm was determined.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 84-87